2018
DOI: 10.3390/fishes3010001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Gene Expression of Zebrafish (Danio rerio) Related to Sterol Uptake and Excretion upon β-Sitosterol Administration

Abstract: Replacement of fishmeal with plant ingredients will introduce not only plant oil and protein but also phytosterol to the fish diet. Mammals strictly restrict the uptake of phytosterol at intestinal epithelial cells by regulating the gene expressions of sterol uptake and excretion proteins; however, phytosterol is found in the fish muscle and other organs. In order to assess the ability of phytosterol uptake by the intestinal epithelial cells of fish, no-sterol diet, cholesterol-, and β-sitosterol-containing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, in our study npc1l1 gene did not respond to 5.1% dietary cholesterol treatment. Another study that employed 3% purified cholesterol also did not report any change in the expression of npc1l1 in the zebrafish intestine ( 58 ). This indicates that a homeostasis maintenance to regulate the absorption of cholesterol through the downregulation of npc1l1 gene expression is probably missing in zebrafish intestine.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study npc1l1 gene did not respond to 5.1% dietary cholesterol treatment. Another study that employed 3% purified cholesterol also did not report any change in the expression of npc1l1 in the zebrafish intestine ( 58 ). This indicates that a homeostasis maintenance to regulate the absorption of cholesterol through the downregulation of npc1l1 gene expression is probably missing in zebrafish intestine.…”
Section: Discussionmentioning
confidence: 99%
“…We grouped male and female fish per treatment for the comparative transcriptome analysis according to the description in previous studies. In this study, the changes in the richness and diversity of gut microbiota communities were independent of sex (Figures S9–S11). Expectedly, data from the qPCR assay revealed that male and female zebrafish shared similar expression patterns in most selected DEGs, suggesting that the generalized signaling pathways induced by TC were unbiased in sex-specific selection.…”
Section: Discussionmentioning
confidence: 99%